2021
DOI: 10.3389/fphys.2021.780490
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Reproduction in a Cooperatively Breeding Mammal: Consequences of Seasonal Variation in Rainfall, Reproduction, and Reproductive Suppression

Abstract: Biological investments, such as reproduction, are influenced by both biotic and abiotic factors and their interactions. The trade-off between reproduction and survival has been well established. Seasonally breeding species, therefore, may exhibit variations in these trade-offs, but there is a dearth of knowledge concerning this. This study investigated the physiological cost of reproduction (measured through oxidative stress) across seasons in the cooperatively breeding highveld mole-rat (Cryptomys hottentotus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 109 publications
(184 reference statements)
0
5
0
Order By: Relevance
“…The social mole-rats were captured and transported as outlined for solitary mole-rats. A subset of animals ( Table 1 ) was sampled within 72 h of being in captivity (similar to other studies [ 79 , 94 ]). An additional subset was maintained under laboratory conditions for more than six months before sampling.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The social mole-rats were captured and transported as outlined for solitary mole-rats. A subset of animals ( Table 1 ) was sampled within 72 h of being in captivity (similar to other studies [ 79 , 94 ]). An additional subset was maintained under laboratory conditions for more than six months before sampling.…”
Section: Methodsmentioning
confidence: 99%
“…All animals used in this study were considered adults and reproductively inactive (non-breeders) {see Bennett and Faulkes [125] on how reproductive status was determined} (Table 1). The use of non-breeders avoids complications between breeder and non-breeder comparisons associated with oxidative stress due to reproduction [74,79] and the effects of reproductive suppression differences [74,79,[98][99][100][101][102][103][104][105][106]125,126] (Supplementary File S1).…”
Section: Social Mole-ratsmentioning
confidence: 99%
See 2 more Smart Citations
“…Medger [1] also eluded to the variation in the longevity between breeders and subordinates in social mole-rat species, which is a point of interest for many researchers [23][24][25][26][27][28]. Medger [1] suggested that the lower oxidative damage found in breeding females of the Damaraland mole-rat contributes to their longer lifespan [29] but does not mention that the opposite trend is seen in naked mole-rats [28].…”
mentioning
confidence: 99%